A Study of Financial Inclusion and Women's Empowerment in South Africa : The Case of Female Entrepreneurs in Gauteng - Zondi, Siphamandla (University of Pretoria, 2021)
Thesis (PhD (Political Science))--University of Pretoria, 2020.